Menopausal Symptoms and Coping Strategies among Women of 40-60 Years Age-Group: A Tertiary Care Hospital Experience from Bangladesh (Community Based Medical Journal, 2025)
A cross-sectional, descriptive study was conducted, in the Department of Obstetrics & Gynaecology, of Community Based Medical College, Bangladesh (CBMC,B) Hospital, Mymensingh, Bangladesh,  on 120 women aged between 40 and 60 years to assess their menopausal symptoms and coping strategies. Exclusion criteria included pregnancy, breastfeeding, or any other significant medical conditions. A semi-structured, pre-tested questionnaire based on modification of Menopausal Rating Scale (MRS) was used to assess their demographic characteristics, menopausal symptoms, and coping strategies, e.g., exercise and dietary adjustments. We also examined BMI of the participants. Participants were categorized based on menopausal status: 46.67% premenopausal, 31.67% perimenopausal, and 21.66% postmenopausal. Graduates represent the most significant education group (34%). Marriage (46.67%), widowhood (29.16%), and divorce (15.83%) are common marital statuses. Economic status varies, with the middle category prevalent (30.70%) and lower status at 14.70%. In BMI, most of the participants were found overweight (42%) or obese (27%). Menopausal symptoms include joint/muscle discomfort (70.60%), exhaustion (61.30%), and sleeping problems (59.30%). Coping strategies include self-calming (76%), exercise, diet awareness (69%), social relationships (63%), sense of achievement (38%), and creative activities (46%). Significant p-values were observed among the groups in self-calming skill, social relationship, and sense of achievement (p0.05). Our data suggests that some women may start experiencing symptoms earlier during perimenopause, while others may notice those later. It is essential to employ different coping strategies, such as building strong social support networks, to improve the wellness of women across such crucial phases of their lives.  CBMJ 2025 January: Vol. 14 No. 01 P: 54-60